Volunsharing of Lenggong Valley world heritage site: A content analysis/ Norliza Aminudin, Maisarah Mohamad Nazary and Salamiah A. Jamal. - Aminudin, Norliza; Mohamad Nazary, Maisarah; A. Jamal, Salamiah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
UNESCO World Heritage Sites (WHS) has the ability to attract diverse domestic and international tourists’ visitation. Malaysia being blessed with four WHSs unfortunately faces a decline in tourist arrivals in one of them, which is the Archaeological Heritage of the Lenggong Valley (AHLV). In combating the issue, a volunsharing program was proposed by the authority, nonetheless it was yet to be materialised. Volunsharing is where volunteers share their holiday experiences at tourism destinations through social media by using word-of-picture. This study aims to investigate the effect of volunsharing through Instagram content analysis via #lenggong. It examines post frequencies, comment slant, total engagement values and exploring emerging themes for captions frequently used in Instagram tourism-related post. Deductive content analysis and thematic analysis are used as the study’s methodology, based on Framing Theory and word-of-picture (WOP) dimensions. Results show that the portrayal of Lenggong Valley as a tourism destination and a WHS is poor. A total of 1,549 posts were analysed and only 290 posts were deemed tourism WOP post, including five thematic captions emerged throughout the six months period sample of this study. The theoretical and practical contributions of this study are discussed.